O senso de justiça como base para a tomada de decisões judiciais - Feldens, Guilherme de Oliveira (Universidade do Vale do Rio dos Sinos, 2014)
The sense of justice is one of the essential elements for the creation of a fair and democratic community as presented in A theory of justice. Rawls's political shift, focusing on the analysis of social stability and legitimacy of power before the plural moral concepts present in current societies, has not totally eliminated the relevance of the sense of justice in the public justification proposed in Political liberalism. In this sense, it is said that morality in Rawls has a social function, once it aims at defending the individual before society without external coercion as a main source of motivation to fulfill its precepts. Based on this picture, the purpose of this study is to show that Rawls presents a concept of Law based on principles of justice expressed in the constitutional settlement. Rawls establishes a model for the legal system distant from legal positivism and utilitarianism, one that is capable of assuring a different democratic sense, distant from the mere attempt to legitimize political authority through a normative discourse. Finally, it is concluded that such model assures a jurisdictional activity characterized by the responsibility to make all citizens in the constitutional settlement accept the justice criteria. Thus, decisions regarding essential social issues shall not be influenced by interests of the transient majorities, nor by the individual moral conceptions of the judges, this way respecting the coherence of a legal system built on democratic judgments.
Keywords: Court decision; Democracy; Law; Sense of justice; Decisão judicial; Democracia; Direito; Senso de justiça; ACCNPQ::Ciências Humanas::Filosofia